2023
DOI: 10.1021/acsami.3c02888
|View full text |Cite
|
Sign up to set email alerts
|

Pore Size Tunable Trypsin@ZIF-90 and Hydrogel Integrated Lateral Flow Point-of-Care Platform for ATP Detection

Abstract: The cost-effective, convenient, visible, and equipment-free determination of biomarkers is always the priority development concern of disease diagnosis. The paper-based signal output strategy permits output visual signals without instruments and is regarded as a promising approach with simple operation and low cost. Herein, by varying the addition amount of trypsin, we pioneered a novel enzyme mineralization strategy to construct trypsin@ZIF-90 with tunable porosity properties and catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…The results suggested that Au/Pt NPs were simply physically trapped within the ZIF-90 framework without participating in the crystallization process of ZIF-90. Building upon our previous work, 35 these results further substantiate the discernible dissimilarity in the mechanisms employed for bioenzymes and nanoenzymes encapsulation utilizing ZIF-90. The nitrogen adsorption isotherms and the pore size distribution data obtained through FLDFT calculations (Figure 2B,C) further support this observation, as they exhibit nearly overlapping characteristics within the same range.…”
Section: ■ Results and Discussionsupporting
confidence: 79%
“…The results suggested that Au/Pt NPs were simply physically trapped within the ZIF-90 framework without participating in the crystallization process of ZIF-90. Building upon our previous work, 35 these results further substantiate the discernible dissimilarity in the mechanisms employed for bioenzymes and nanoenzymes encapsulation utilizing ZIF-90. The nitrogen adsorption isotherms and the pore size distribution data obtained through FLDFT calculations (Figure 2B,C) further support this observation, as they exhibit nearly overlapping characteristics within the same range.…”
Section: ■ Results and Discussionsupporting
confidence: 79%